2020
DOI: 10.3389/fchem.2020.00254
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Tin Sulfide Nano-Sheets as Cathode Material for Lithium-Sulfur Batteries

Abstract: Unprecedented self-assembled hierarchical nano-sheets of SnS were synthesized by the hydrothermal method. In a typical reaction, SnCl 2 .2H 2 O and Na 2 S.9H 2 O were used as reactants. Structural and morphological properties were studied by X-ray diffraction (XRD), and scanning electron microscopy (SEM) while the electrochemical properties were measured by cyclic voltammetry, charge-discharge cycles, and electrochemical impedance spectroscopy (EIS). SEM results showed the 1-D SnS nano-sheets with an average t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…With respect to the electrochemical performances in batteries, although pure SnS nanostructures, such as 0D SnS NPs, [31] 1D SnS nanostructures, [62,66] 2D SnS NSs or nanoplates, [153,184,185] 3D SnS nanoflowers or yolk-shell microstructures, [32,99,186] have made considerable progress in the field of batteries, such as Li or Na-ion batteries and Li-S batteries, yet its low electronic conductivity, large volume expansion and poor cycling stability during charging and discharging, greatly limit its practical applications. To this end, a number of researches has focused on the functionalization of SnS with graphene, [69,101,124,137,158,159] CNTs, [111,112,156,187] C fibers, [28,30,146] conductive polymers, [138] MoS 2 NSs, [116,147,150] etc., to achieve outstanding electrochemical performances.…”
Section: Batteries and Solar Cellsmentioning
confidence: 99%
“…With respect to the electrochemical performances in batteries, although pure SnS nanostructures, such as 0D SnS NPs, [31] 1D SnS nanostructures, [62,66] 2D SnS NSs or nanoplates, [153,184,185] 3D SnS nanoflowers or yolk-shell microstructures, [32,99,186] have made considerable progress in the field of batteries, such as Li or Na-ion batteries and Li-S batteries, yet its low electronic conductivity, large volume expansion and poor cycling stability during charging and discharging, greatly limit its practical applications. To this end, a number of researches has focused on the functionalization of SnS with graphene, [69,101,124,137,158,159] CNTs, [111,112,156,187] C fibers, [28,30,146] conductive polymers, [138] MoS 2 NSs, [116,147,150] etc., to achieve outstanding electrochemical performances.…”
Section: Batteries and Solar Cellsmentioning
confidence: 99%
“…Group IV–VI binary compounds, which contain elements from both groups IV and VI of the periodic table, have garnered attention as electrode materials in metal-ion batteries as a consequence of their generous capacity, good rate performance, and low cost. These compounds have been scrutinized as electrode materials and include 2D nanosheets, such as tin sulfide (SnS), germanium sulfide (GeS), and tin selenide (SnSe). Inspired by the systematic investigation of the two different phases of SiS nanosheets by Yang et al, the intention of this study is to evaluate the potential of the puckered phase of 2D silicon monosulfide (α-SiS), similar to black phosphorene, as an anode material for use in multivalent metal-ion batteries. Through the utilization of the density functional theory (DFT), this study examined the structural and electronic attributes of the α-SiS nanosheet, aiming to assess its suitability as an anode material in metal-ion batteries, including the total and projected density of states (TDOS and PDOS) and variations in three-dimensional (3D) charge density distribution of metal ions, such as Na, Ca, and Al ions, on the exterior of the α-SiS nanosheet.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the cubic or tetragonal crystal phase of SnNPs provides a combination space for biological recognition molecules, such as aptamers [ 27 , 28 ]. Furthermore, the high electronic conductivity [ 29 ] and high specific capacity [ 30 ] of SnNPs will improve electronic machinery in electrochemical sensing technologies. To date, several studies have been reported on SnO 2 -based electrochemical sensors for small metal detection [ 31 , 32 ], but no studies have been published on SnNPs-based electrochemical aptasensors in biomedical diagnostics.…”
Section: Introductionmentioning
confidence: 99%